The digital euro: A precautionary device, not a deus ex machina - Ignazio Angeloni (Leibniz Institute for Financial Research SAFE, 2023)
There is much discussion today about a possible digital euro (PDE). Is this attention exaggerated? Are "central bank digital currencies" (CBDCs) "a solution in search of a problem", as some have argued? This article summarizes the main facts about the PDE and concludes that, if the decision on adoption had to be taken today, the arguments against would outweigh those in favor. However, there may be future circumstances in which having a CBDC ready for use can indeed be useful. Therefore, preparing is a good thing, even if the odds of its usefulness in normal conditions are slim.
Keywords: 330; Digital; Euro; Financial Stability; Monetary Policy; Central Bank; CBDC; Banks